Select microbial metabolites in the small intestinal lumen regulates vagal activity via receptor-mediated signaling - Kelly G. Jameson; Sabeen A. Kazmi; Takahiro E. Ohara; Celine Son; Kristie B. Yu; Donya Mazdeyasnan; Emma Leshan; Helen E. Vuong; Jorge Paramo; Arlene Lopez-Romero; Long Yang; Felix E. Schweizer; et al. (iScience)
Summary: The vagus nerve is proposed to enable communication between the gut microbiome and the brain, but activity-based evidence is lacking. We find that mice reared germ-free exhibit decreased vagal tone relative to colonized controls, which is reversed via microbiota restoration. Perfusing antibiotics into the small intestines of conventional mice, but not germ-free mice, acutely decreases vagal activity which is restored upon re-perfusion with intestinal filtrates from conventional, but not germ-free, mice. Microbiome-dependent short-chain fatty acids, bile acids, and 3-indoxyl sulfate indirectly stimulate vagal activity in a receptor-dependent manner. Serial perfusion of each metabolite class activates both shared and distinct neuronal subsets with varied response kinetics. Metabolite-induced and receptor-dependent increases in vagal activity correspond with the activation of brainstem neurons. Results from this study reveal that the gut microbiome regulates select metabolites in the intestinal lumen that differentially activate vagal afferent neurons, thereby enabling the microbial modulation of chemosensory signals for gut-brain communication.